Continuing Professional Development for Lecturers at the National University of Lesotho: Milestones and Challenges - Tlali, Tebello (International Journal of African Higher Education, 2019)
This article appraises efforts by the National University of Lesotho (NUL) to provide continuing professional development for lecturers. The findings of a previous study suggested that the majority of lecturers at this university were not trained as teachers and that this could negatively impact on their teaching. The establishment of a staff academic development center was long overdue. In April 2014, the university established the Centre for Teaching and Learning (CTL). Drawing on a constructivist perspective, a qualitative approach was adopted to explore the current situation. The findings indicate that efforts to roll out continuing professional development for lecturers have not borne any significant results. The problem is exacerbated by a lack of support from the university community as well as lecturers’ poor attendance at the staff academic development workshops hosted by the CTL. It is thus recommended that management put mechanisms in place to support the center and ensure compulsory staff participation. Cet article vise à évaluer les moyens mis en place par l’Université Nationale du Lesotho (National University of Lesotho ou NUL) pour offrir une formation professionnelle continue aux Maîtres de conférence. Une précédente recherche a démontré que la majorité des Maîtres de conférence de cette université ne recevait pas de formation en tant qu’enseignants, ce qui pouvait avoir un impact négatif sur leur activité d’enseignement. Il était donc grand temps de créer un centre de formation pour le personnel universitaire. En avril 2014, l’université a inauguré un Centre d’Enseignement et d’Apprentissage (Centre for Teaching and Learning ou CTL). A partir d’un point de vue constructiviste, la situation actuelle a été examinée selon une approche qualitative. Les résultats de cette recherche indiquent que les moyens mis en place pour proposer aux Maîtres de conférence une formation professionnelle continue n’ont pas été concluants. Le problème est accentué par un manque de soutien de la part de la communauté universitaire et par les absences répétées des Maîtres de conférence aux ateliers de formation organisés par le CTL pour le personnel universitaire. Il serait pertinent que la direction mette en place des mécanismes permettant de soutenir le Centre et de rendre la participation du personnel obligatoire.